PERANCANGAN SISTEM INFORMASI MANUFAKTUR DI LABORATORIUM PLASTIK INJEKSI POLITEKNIK MANUFAKTUR ASTRA - Fonda Arifianto, Mada Jimmy; Santoso, Edi (Industrial and Systems Engineering Assessment Journal (INASEA), 2004)
Article presents manufacture information system design in Astra manufacture institute injection plastic laboratory. In manufacture process, the working productivity is increase to lowered the costs. Information system on manufacture process needs to defined more detail and specific so the information can be access transparantly and the miss use of information did not happen. Manufacture information system can support the whole production process to produce high quality product, precise, and with low costs.